Mediating Role of Dividend Policy on the Effect of Profitability, Company Size, and Capital Structure on the Value of Manufacturing Companies in the Indonesia Stock Exchange - Simanjuntak, Yuliana Efriani Kristianingsih; Sihotang, Ronny Buha; Hutabarat, Francis (IJBLE Scientific Publications Community Inc., 2024)
This study aims to analyze and prove (1) the effect of Profitability, company size, and capital structure partially and simultaneously on the value of Manufacturing companies on the IDX. The problem in manufacturing companies is that there is still an uneven distribution of dividends, which can affect company value. The population of this study were all manufacturing companies on the IDX using purposive sampling technique, namely sample withdrawal based on specific criteria. This type of research is quantitative descriptive research, which aims to describe or describe the properties (characteristics) of a situation or research object, carried out through quantitative data collection and analysis and statistical testing. This research test tool uses multiple linear regression models, such as the t-test and F-test. The results of this study prove that Profitability, company size, capital structure, and dividend policy simultaneously affect the value of manufacturing companies on the IDX. Partial test results prove that company size and capital structure affect the value of manufacturing companies on the IDX, while profitability and dividend policy do not affect the value of manufacturing companies on the IDX. The results of path analysis testing prove that Profitability through dividend policy affects firm value. Company size through dividend policy does not affect firm value. Capital structure through dividend policy does not affect firm value.